Synthesis of NaY Zeolite Using Mixed Calcined Kaolins - Subagjo Subagjo; Endang Sri Rahayu; Tjokorde Walmiki Samadhi; Melia Laniwati Gunawan (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
Kaolin is one of several types of clay minerals. The most common crystalline phase constituting kaolin minerals is kaolinite, with the chemical composition Al2Si2O5(OH)4. Kaolin is mostly used for manufacturing traditional ceramics and also to synthesize zeolites or molecular sieves. The Si-O and Al-O structures in kaolin are inactive and inert, so activation by calcination is required. This work studies the conversion of kaolin originating from Bangka island in Indonesia into calcined kaolin phase as precursor in NaY zeolite synthesis. In the calcination process, the kaolinite undergoes phase transformations from metakaolin to mullite. The Bangka kaolin is 74.3% crystalline, predominantly composed of kaolinite, and 25.7% amorphous, with an SiO2/Al2O3 mass ratio of 1.64. Thermal characterization using simultaneous DSC/TGA identified an endothermic peak at 527°C and an exothermic peak at 1013°C. Thus, three calcination temperatures (700, 1013, and 1050 °C) were selected to produce calcined kaolins with different phase distributions. The best product, with 87.8% NaY zeolite in the 54.7% crystalline product and an SiO2/Al2O3 molar ratio of 5.35, was obtained through hydrothermal synthesis using mixed calcined kaolins with a composition of K700C : K1013C : K1050C = 10 : 85 : 5 in %-mass, with seed addition, at a temperature of 93 °Cand a reaction time of 15 hours.